Disaster preparedness module for resilience building among schoolchildren: A case study of floods in Kerala, India - Mubarak, Niseetha Parveen; Akhir, Noremy Md.; Mohamad, Mohd Suhaimi (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Building resilience among schoolchildren in flood-prone Kerala, India, is essential due to the recurring and severe impacts of floods. The 2018 floods and subsequent events led to widespread displacement, prolonged school closures, and disruptions to children's emotional and social support systems. This study explores disaster preparedness characteristics, coping mechanisms, and essential psychosocial skills among children to develop a child-centred disaster preparedness module. Adopting a qualitative case study design, data were collected through four focus group discussions with 32 schoolchildren, and interviews with six parents and four school social workers. Thematic analysis was conducted manually using Braun and Clarke’s six-step method, identifying themes considered as module section under three parts: disaster preparedness characteristics, including understanding flood hazards, articulation, support and collaboration; coping mechanisms, including emotional regulation, information management and exposure control, resilient behavior, and general health awareness; and psychosocial skills, including life skills, socio-spatial skills, cognitive skills, and skill-based preparedness. The proposed disaster preparedness module is intended for implemented in school curricula to enhance psychosocial readiness and confidence among children.